The Post-Truth Era and Fake News - Farah Hasan; Sanaa Hassan (مجلة الآداب, 2024)
Post-Truth Era is a term used recently by The Oxford Dictionary and it deals with facts have no much importance in our current world. People show no interest to know the truth and they believe what match their interests and desires. Disinformation, misinformation, alternative facts and fake news are the phenomena of the post-truth era. Correlating the information becomes more complicated, challengeable and devastating due to technological development. Therefore, post-truth is a sort of ideological superiority in which its proponents attempt to force someone to accept a belief whether or not it is supported by solid facts. Currently, individuals are misled and manipulated by fake news. Thus, the study gives much weight to the importance of understanding the post-truth era. It argues that post-truth discourse has influenced the perception of people. Moreover, it emphasizes that the current era is but an illusion and has nothing to do with truth since it has completely disappeared and is represented by chaos and apathy.